Models Used to Select Strategic Planning Experts for High Technology Productions; IOP Conference Series: Materials Science and Engineering; Vol. 127 : Urgent Problems of Modern Mechanical Engineering - Zakharova A. A. Aleksandra Aleksandrovna; Grigoreva A. A. Antonina Alekseevna; Tseplit A. P. Anna; Ozgogov E. V. Evgenij (2016, 2016)
Title screen